Social and technological aspects of disaster resilience. Issue 3 (2nd July 2016) - Giuliani, Luisa; Revez, Alexandra; Sparf, Jorgen; Jayasena, Suranga; Havbro Faber, Michael
ABSTRACT: Large scale projects tasked with designing infrastructures and urban networks resilient to disasters face a common challenge, i.e. the need to address concomitant technological issues and social problems. What is more, conflicting technologies and the diverse philosophical underpinnings of distinct academic disciplines pose difficulties in the collaboration among experts of different fields. These difficulties and possible ways to tackle them have been highlighted by a questionnaire developed in the framework of an EU project named ANDRDD (Academic Network for Disaster Resilience to optimize Educational development). More specifically, the project investigated the level of interdisciplinary work in current research and educational projects within the field of disaster resilience. findings illustrate the number and types of disciplines involved in disaster resilience projects and suggest that a higher degree of integration between different disciplines in tertiary education could promote a transdisciplinary approach to disaster resilience, resulting in design efficiency and innovation.